The nutritional value of meat should be considered when comparing the carbon footprint of lambs produced on different finishing diets - McNicol, Louise C.; Perkins, Lynda S.; Gibbons, James; Scollan, Nigel D.; Nugent, Anne P.; Thomas, Eleri M.; Swancott, Elizabeth L.; McRoberts, Colin; White, Alison; Chambers, Simon; Farmer, Linda; Williams, A. Prysor (Frontiers in Sustainable Food Systems, 2024)
Lamb production systems are under increasing pressure to reduce their environmental footprint, particularly emissions of greenhouse gases (GHGs) such as methane. However, the metrics used to express the carbon footprint of lamb seldom consider its nutritional density and contribution to balanced diets in humans. Lamb production systems vary considerably, from low-input pastoral systems to higher-input systems feeding concentrates for the latter 'finishing' period. To date, no studies have explored the effect of finishing diet on the carbon footprint of lamb meat on a nutritional basis. Data from 444 carcasses were collected from four abattoirs across Wales, UK. Lambs were derived from 33 farms with one of four distinct finishing diets: forage crops (n=5), grass (n=11), concentrates (n=7), and grass and concentrates (n=15). Carcass data were analysed using mixed effects models. Significant differences were found in fatty acid composition of two large commercial cuts of meat from different finishing diets. To illustrate the effect of different measures of footprint, mass (kg dwt) and omega-3 polyunsaturated fatty acid content (g omega-3) were selected as functional units. GHG emission estimates were calculated using Agrecalc. The concentrates diet had the lowest average mass-based product emissions (25.0 kg CO2e/kg deadweight (dwt)) whilst the grass systems had the highest (28.1 kg CO2e/kg dwt) (p<0.001). The semimembranosus muscle cut from the forage crops diet had the lowest average nutrition-based product emissions (19.2 kg CO2e/g omega-3); whereas the same muscle cut from lambs finished on the grass and concentrates diet had the highest nutrition-based product emissions (29.4 kg CO2e/g omega-3) (p<0.001). While mass-based functional units can be useful for comparing efficiencies of different farming systems, they do not reflect how farming systems impact the nutritional differences of the final product. This study demonstrates the importance of considering nutrition when expressing and comparing the carbon footprints of nutrientdense foods such as lamb. This approach could also help inform discussions around the optimal diets for lamb production systems from both a human nutrition and environmental sustainability perspective.